A Fresh Look at the Unconscious Thought Effect: Using Mind-Wandering Measures to Investigate Thought Processes in Decision Problems With High Information Load - Steindorf, Lena; Rummel, Jan; Boywitt, C. Dennis (Frontiers in Psychology, 2021)
Unconscious Thought Theory (Dijksterhuis, 2004) states that thinking about a complex problem unconsciously can result in better solutions than conscious elaboration. We take a fresh look at the cognitive processes underlying “unconscious” thought by analyzing data of 822 participants who worked on a complex apartment-evaluation task in three experiments. This task’s information-presentation and evaluation parts were separated by different kinds of filler-interval activities, which corresponded to standard conscious-thought and unconscious-thought manipulations. Employing experience-sampling methods, we obtained thought reports during and after filler-interval engagement. Evidence concerning the existence of the Unconscious Thought Effect was mixed, with such an effect being present in the first two experiments only. In these experiments, we further found that less problem deliberation is associated with better performance on the apartment task. Interestingly, this benefit disappeared when we probed participants’ thoughts during the filler interval. We suggested that explicit thought awareness diminishes the Unconscious Thought Effect.